Critical heat flux enhancement in water-based nanofluid with honeycomb porous plate on large heated surface - Suazlan, Mt Aznam; Shoji, Mori; Kunito, Okuyama (The American Society of Mechanical Engineers, 2016)
Heat removal through pool boiling is limited by the phenomena of critical heat flux (CHF). CHF enhancement is vitally important in order to satisfy demand for the cooling technology with high heat flux in In Vessel Retention (IVR). Various surface modifications of the boiling surface, e.g., integrated surface structures and coating of a micro-porous have been proven to effectively enhance the CHF in saturated pool boiling. We have been proposed a novel method of attaching a honeycomb structured porous plate on a considerably large heater surface. Previous results, by the authors in [1] reported that CHF has been enhanced experimentally up to more than approximately twice that of a plain surface (approximately 2.0 to 2.5 MW/m2 ) with a diameter of 30 mm heated surface. However, it is necessary to demonstrate the method together with infinite heater surface within laboratory scale. It is important that cooling techniques for IVR could be applicable to a large heated surface as well as remove high heat flux. Objective of this study is to investigate the CHF of honeycomb porous plate and metal solid structure in nanofluid boiling or water boiling on a large heated surface. Water-based nanofluid offers good wettability and capillarity. While metal solid structure is installed on honeycomb porous plate to increase the number of vapor jet. Experimental results of honeycomb porous plate and combination of honeycomb porous plate and metal solid structure in water-based nanofluid boiling shows that CHF is increased up to twice [2] and thrice, respectively compared to plain surface in water boiling. To the best of the author’s knowledge, the highest value (3.1 MW/m2 ) was obtained for a large heated surface having a diameter of 50 mm which is regarded as infinite heated surface. This demonstrates potential for general applicability to have more safety margin in IVR method.